Cell‐Derived Extracellular Matrix‐Rich Biomimetic Substrate Supports Podocyte Proliferation, Differentiation, and Maintenance of Native Phenotype. (19th February 2020) - Satyam, Abhigyan; Tsokos, Maria G.; Tresback, Jason S.; Zeugolis, Dimitrios I.; Tsokos, George C.
Abstract: Current technologies and available scaffold materials do not support long‐term cell viability, differentiation, and maintenance of podocytes, the ultra‐specialized kidney resident cells that are responsible for the filtration of the blood. A new platform which imitates the native kidney microenvironment by decellularizing fibroblasts grown on surfaces with macromolecular crowding is developed. Human immortalized podocytes cultured on this platform display superior viability and metabolic activity up to 28 days compared to podocytes cultured on tissue culture plastic surfaces. The new platform displays a softer surface and an abundance of growth factors and associated molecules. More importantly, it enables podocytes to display molecules responsible for their structure and function and a superior development of intercellular connections/interdigitations, consistent with maturation. The new platform can be used to study podocyte biology, test drug toxicity, and determine whether sera from patients with podocytopathies are involved in the expression of glomerular pathology. Abstract : A new culture system based on a cell‐derived decellularized matrix allows enhanced survival and differentiation of podocytes in vitro. Specifically, fibroblasts are grown in the presence of macromolecular crowding on plates to form monolayers and are subsequently decellularized. Podocytes survive and differentiate on plates coated with decellularized matrices significantly better than on non‐coated plates.